2015
DOI: 10.1016/j.jcv.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of nosocomial and community-acquired influenza in a large university hospital during two consecutive influenza seasons

Abstract: Despite the different distribution of virus subtypes and epidemiological properties between both influenza seasons, the rate of nosocomial cases remained similar. Systematic detection and targeted prevention measures seem mandatory to minimize nosocomial influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 17 publications
4
29
8
Order By: Relevance
“…8 A German group recently reported the proportion of hospital-acquired influenza virus infection as 20.5%-24.6%. 9 Our rate of such infections (28.1%) was somewhat higher than prior reports. Our inclusion of pediatric patients may have been responsible for this.…”
Section: Discussioncontrasting
confidence: 69%
“…8 A German group recently reported the proportion of hospital-acquired influenza virus infection as 20.5%-24.6%. 9 Our rate of such infections (28.1%) was somewhat higher than prior reports. Our inclusion of pediatric patients may have been responsible for this.…”
Section: Discussioncontrasting
confidence: 69%
“…In a study over two influenza seasons in Germany, Huzly et al reported a rate of nosocomial transmission of 24% (2012–2013) and 20% (2013–2014) (54). Specific guidelines are available to help prevent transmission of infectious pathogens through isolation precautions (55).…”
Section: Other Viruses Leading To Ardsmentioning
confidence: 99%
“…In a tertiary care hospital in France, during the 2016-2017 in uenza A season, 25% of hospitalized infection cases were considered hospital-acquired infection [12] . A German university hospital reported 24% hospital-acquired infection cases in the 2012-2013 in uenza season and 20% in the 2013-2014 season [5] . However, a lower proportion of hospital-acquired cases have been observed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-acquired in uenza may be associated with poor prognosis. In Germany, a case fatality rate of 9% has been reported, which was mainly associated with in uenza virus A(H1N1) pdm09 [5] , and in Sweden, a hospital-acquired in uenza A case fatality rate of 9.6% has been reported [6] . Moreover, hospital-acquired in uenza A infection has been reported to be an independent factor associated with mortality among patients admitted to an intensive care unit (ICU) [7] .…”
Section: Introductionmentioning
confidence: 99%